Functional identification of MdSMXL8.2, the homologous gene of strigolactones pathway repressor protein gene in Malus × domestica - Weijian Sun; Xinglong Ji; Laiqing Song; Xiaofei Wang; Chunxiang You; Yujin Hao (Horticultural Plant Journal, 2021)
A homologous gene of strigolactones repressor protein gene SMXL7/D53, MdSMXL8.2 (GenBank accession No.: MD07G1222400), was cloned from ‘Royal Gala’ apple (Malus × domestica Borkh.) in this study. The sequence analysis revealed that the length of this gene was 3 243 bp, which encoded 1 080 amino acids, and had a protein molecular mass of ∼110 kD. The phylogenetic tree analysis indicated that the MdSMXL8.2 exhibited the highest sequence similarity with Arabidopsis AtSMXL7. The protein conserved domain analysis revealed that the MdSMXL8.2 contained two ClpA domains. The prediction of the secondary and tertiary structures of the MdSMXL8.2 indicated that it contained 34.54% α helix, 3.43% β-sheet, and 11.76% extended chain. The in-silico analysis suggested that the promoter sequence of MdSMXL8.2 contained several typical cis-acting elements, including abscisic acid (ABA), gibberellin (GA), ethylene, auxin, jasmonic acid (JA), salicylic acid (SA), drought, and heat stress-responsive elements. Quantitative real-time (qRT)-PCR analyses revealed that MdSMXL8.2 was expressed in different apple tissues, with the highest transcript level found in the stem. The expression of MdSMXL8.2 was significantly induced by exogenous ABA, PEG and mannitol, while exogenous NaCl significantly inhibited MdSMXL8.2 expression. The growing status of MdSMXL8.2-overexpressed Orin apple callus was worse than the wild type (WT) after NaCl treatment and had a higher malondialdehyde (MDA) content and relative conductance (REC). Additionally, MdSMXL8.2-overexpressed Arabidopsis exhibited shorter root length and a reduction in fresh weight under salt stress, indicating that MdSMXL8.2 negatively regulated salt tolerance in apples.